Teaching in Higher Education after COVID-19: Optimizing Faculty Time and Effort Using a Proposed Model - Naeem Bajwa; Thomas Tudor; Otmar Varela; Karen Leonard (MDPI AG, 2024)
We propose a model for use in higher education after COVID-19 that addresses how to organize class methods for effective and efficient teaching outcomes for both students and instructors. Faculty have a finite amount of time that they may spend on their courses and must determine which time combinations produce the best outcomes. First, we discuss the key work-related challenges faced by faculty and contend that competing demands on faculty time result in inefficient allocation of their time and effort. We then model the issue as an optimization problem and illustrate through examples how to help faculty choose optimal method combinations along with time spent. We use time as a measure of effort and define which combination of methods might be most effective for achieving course learning objectives. There are opportunities for wider use of this methodology, as effective application of effort toward meeting the appropriate learning objectives should create better outcomes. Numerical examples are used to demonstrate the applicability of the proposed model, including how administrators can use it to support and encourage faculty.